Keap1/Nrf2 Signaling: A New Player in Thyroid Pathophysiology and Thyroid Cancer - Renaud, Cedric O.; Ziros, Panos G.; Chartoumpekis, Dionysios V.; Bongiovanni, Massimo; Sykiotis, Gerasimos P. (Frontiers in Endocrinology, 2019)
ABSTRACT The Keap1/Nrf2 pathway is a key mediator of general redox and tissue-specific homeostasis. It also exerts a dual role in cancer, by preventing cell transformation of normal cells but promoting aggressiveness and drug resistance of malignant ones. Although Nrf2 is well-studied in other tissues, its roles in the thyroid gland are only recently emerging. This review focuses on the involvement of Keap1/Nrf2 signaling in thyroid physiology and pathophysiology in general and particularly in thyroid cancer. Studies in mice and cultured follicular cells have shown that, under physiological conditions, Nrf2 coordinates antioxidant defenses and directly increases thyroglobulin production and inhibits its iodination. Increased Nrf2 pathway activation has been reported in two independent families with multinodular goiters due to germline loss-of-function mutations in KEAP1. Nrf2 pathway activation has also been documented in papillary thyroid carcinoma (PTC), due to somatic mutations or epigenetic modifications in KEAP1 or other pathway components. In PTC, such Nrf2-activating KEAP1 mutations have been associated with tumor aggressiveness. Furthermore, polymorphisms in the prototypical Nrf2 target genes NQO1 and NQO2 have been associated with extra-thyroidal extension and metastasis, respectively. More recently, mutations in the Nrf2 pathway have also been found in Hürthle-cell (oncocytic) thyroid carcinoma. Finally, in in vitro and in vivo models of poorly-differentiated and undifferentiated (anaplastic) thyroid carcinoma, Nrf2 activation has been associated with resistance to experimental molecularly-targeted therapy. Thus, Keap1/Nrf2 signaling is involved in both benign and malignant thyroid conditions, where it might serve as a prognostic marker or therapeutic target.